PENGARUH KECEPATAN ARUS, CEPAT RAMBAT GELOMBANG, DAN UKURAN PARTIKEL SEDIMEN TERHADAP VOLUME ANGKUTAN SEDIMEN - Aditya Dharma Putra; Rifardi '; Musrifin Ghalib (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study was conducted from March to April 2016 in the Laboratory of PhysicalOceanography Marine Science Department Faculty of Fisheries and Marine Science University ofRiau. This study aimed to explain a relationship between current velocity and wave propagationspeed, and sediment particle size to the results of sediment transport volume. The method used wasan experimental design with 4 treatments. Current velocity and wave propagation speed wereconsists of 2 level factors (V1 and V2) and sediment particle size were consists of 2 level factors(D1 and D2). Observations used the flume tank and wave generator for 10 minutes. The resultsshow that there was an effect of current velocity, wave propagation, and sediment particle size tosediment transport volume. If the current velocity increase so sediment transport volume alsoincreased. While if sediment particle size increase the sediment transport volume decreased.Observations in the laboratory and calculation of sediment transport that used an Engelund-Hansenformula showed differences. Differences caused by oceanographic factors such as water andsediment density, gravity, water depth, salinity and consistency.Keywords: The Volume of Sediment Transport, Current, Wave, Particle, Velocity.